Muslim states and the implementation of the convention on the rights of the child: with special reference to Malaysia - Hamid, Abdul Ghafur@Khin Maung Sein (Brill: Martinus Nijhoff Publishers, 2013)
The Convention on the Rights of the Child (CRC)1 is the most widely adopted international human rights treaty of the time, and almost all Muslim States are parties to the treaty. This contribution seeks to examine the issues and challenges that Muslim States are faced with in the imple mentation of the CRC. It first reviews the various reservations entered by Muslim States and distinguishes between those based on Islamic law (Sharī‘ah) and those based on domestic laws or national policies of the State concerned.